POLA DAN ESENSI KORDINASI DALAM PELAYANAN eKTP DI KOTA KENDARI - Jamal Bake; La Ode Mustafa; Zulfiah Larisu; Akbar Wahbi (Journal Publicuho, 2022)
The research question is how to implement coordination in the electronic Resident Card or eKTP service in Kendari City.The study used a qualitative approach, collecting data by interviewing selected informants, studying documents from relevant agencies and other sources, and analyzed descriptively according to the Miles and Huberman interaction model. In conclusion, the implementation of coordination in eKTP services internally involves all elements and parts of the Kendari City Population and Civil Registration Service organization, vertically involving leaders and subordinates and horizontally involving various fields within the organization, between sections with other sections, as well as coordination among fellow employees. staff individually in each section. Externally, vertical coordination involves the Department of Population and Civil Registration with the Director General of Population of the Ministry of Home Affairs, the Provincial Office of Population and Civil Registration, horizontally involving the Central Bureau of Regency Statistics and Bappeda City of Kendari as planners and program makers related to eKTP services, population administration and civil registration, and The diagonal involves the sub-district government, village and sub-district governments in the Kendari City government area.